Soluble soybean polysaccharide films containing in-situ generated silver nanoparticles for antibacterial food packaging applications. (March 2022) - Liu, Jie; Ma, Zhengxin; Liu, Yanchun; Zheng, Xuejing; Pei, Ying; Tang, Keyong
Abstract: In the present study, antibacterial soluble soybean polysaccharide (SSPS)-based nanocomposite films containing in-situ generated silver nanoparticles (AgNPs) were fabricated for food packaging applications. SSPS first reduced silver ions to AgNPs in aqueous solution, and then immobilized these nanoparticles via film casting and drying methods. The formation and homogeneously distribution of AgNPs in glycerol-plasticized SSPS films were confirmed by scanning electron microscopy, energy dispersive X-ray spectroscopy, X-ray photoelectron spectroscopy, X-ray diffraction and transmission electron microscopy. The structure and properties of the SSPS/AgNPs films were characterized via ultraviolet-visible spectroscopy, scanning electron microscopy, thermogravimetry, mechanical testing, water vapor permeability and optical properties measurements. The presence of AgNPs improved the thermal stability and ultra-violet light barrier property of the SSPS films. Antibacterial tests revealed excellent inhibition activity of the SSPS/AgNPs films against different types of bacteria ( Escherichia coli and Staphylococcus aureus ). The SSPS/AgNPs films could be processed into heat-sealed packaging pouches to extend the shelf life of green grapes. Graphical Abstract: ga1 Highlights: Soluble soybean polysaccharide (SSPS)-based nanocomposite films with in-situ generated AgNPs were fabricated. AgNPs were homogeneously distributed in SSPS matrix. AgNPs enhanced UV-barrier and thermal properties of the films. The nanocomposite films exhibited excellent antibacterial activity. Heat-sealed pouches made from the nanocomposite films extended the shelf life of green grapes.